STRATEGY FOR INCREASING WELFARE BASED ON COMMUNITY EMPOWERMENT THROUGH MSME (Village Case Studies Wadas, Subdistrict Kandangan, Regency Temanggung) - Sofwan Baharrudin; Ratih Pratiwi; Ernawati Budi Astuti (International Journal of Management, Business, and Social Sciences, 2022)
Abstract Society is a subject and an object that plays an essential role in welfare—community empowerment through MSME as a strategy to improve the community's interest in Wadas Village. The purpose of this study was to analyze and determine the improvement of the system and improvement of welfare based on community empowerment through MSME in Wadas Village, Kandangan District, Temanggung Regency. This type of research is descriptive qualitative with interview data collection methods centered on key informants (MSME administrators & the general public) and key non-informants (Village Heads) as primary data and the SOP manual for MSME empowerment as secondary data. The data analysis technique used SWOT analysis, and the results were entered into the IFAS, EFAS, and SFAS matrices. The results of this study are community empowerment through MSME can improve the welfare of the community in Wadas Village. The improvement strategy that can be taken is to support an aggressive policy or growth-oriented procedure by taking advantage of existing opportunities and internal strengths in community empowerment through MSME in Wadas Village, Kandangan District, Temanggung Regency. Keyword : Welfare, Strategy, Community Empowerment, MSME